Thermodynamic analysis and numerical optimization of the NET Power oxy-combustion cycle. (15th September 2016) - Scaccabarozzi, Roberto; Gatti, Manuele; Martelli, Emanuele
Highlights: Complete thermodynamic analysis and optimization of the NET Power oxy-combustion cycle. Detailed process simulation developed in Aspen Plus. Optimization-based sensitivity analyses performed to find the key design variables. Optimal cycle features a net electric efficiency (LHV basis) of 54.80% with 100% CO2 capture. Abstract: This paper presents a thorough thermodynamic analysis and optimization of the NET Power cycle (also called Allam cycle), a natural-gas-fired oxy-combustion cycle featuring nearly 100% CO2 capture level, very high net electric efficiency, and potentially near-zero emissions level. The main goals of this study are the systematic optimization of the cycle for the maximum efficiency, and the quantification of the effects of the modelling assumptions and equipment performance on the optimal cycle variables and efficiency. An Aspen Plus flow-sheet featuring accurate first-principle models of the main equipment units (including cooled turbine) and fluid properties (equation of state) has been developed. The influence of the cycle variables on the thermodynamic performance of the cycle is first assessed by means of sensitivity analyses. Then, the cycle variables, which maximize the net electric efficiency, are determined with PGS-COM, a black-box numerical optimization algorithm, linked to the simulation software. The corresponding maximum cycle efficiency is equal to 54.80% (with 100% CO2 capture), confirming the outstanding performance of the NET Power cycle. Moreover, the optimization indicates the existence of promising combinations of the cycle variables which lead to reduced component costs (due to the lower operating pressures and temperatures) of the most critical components, without considerably affecting the net electric efficiency. The analysis also indicates that the cooling medium temperature, the power consumption of the air separation unit, the effectiveness of the regenerator and the effectiveness of the turbine cooling system are the main factors influencing the cycle efficiency.